A preliminary experimental investigation of the effect of surface catalytic efficiency on stagnation point heat transfer - Busing, J. R. (College of Aeronautics, 1962)
Results of an experimental investigation to measure the difference between the heat transfer rate to a catalytic wall and to a non-catalytic wall are presented. Using thin film thermometer techniques, associated with an electrical analogue, direct measurement was made of the heat transfer rate to a chemically deposited platinum film and a vacuum evaporated silicon monoxide film. These films were formed near the stagnation point of a pyrex glass sphere and the experiments were done in the College of Aeronautics shock tube. The models were designed so that the heat transfer rates were measured under identical flow conditions. The results obtained indicate that the heat transfer rate to the platinum film is significantly higher than the heat transfer rate to the silicon monoxide film.